PENGEMBANGAN PRODUK MINUMAN JELI EKSTRAK DAUN HANTAP (Sterculia oblongata R. Brown) SEBAGAI ALTERNATIF PANGAN FUNGSIONAL - Pamungkas, Anggar; Sulaeman, Ahmad; Roosita, Katrin (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2014)
The objective of this study was to develop a jelly drink product based on hantap leaves extract (Sterculia oblongata R. Brown) as an alternative of functional food. Completed randomize nested design with two factor (The type and level of concentration of the gelling agent) was applied in this study and resulted in nine formulas. The selected jelly drink formula was determined by preference test using semitrained panelists. Jelly drink with the addition of a gelling agent carrageenan with a concentration level of 0.20% and melon flavor was preferred by 86% panelist. This formula contained 87.37% water, 0.18% ash, 0.10% protein, 0.04% fat, 12.3% carbohidrate, 2.08% fiber, 10.6 mg/100g total phenols, 0.68 mg/100g vitamin C and antioxidant activity 20.92 % with IC50 values is 464.02μL. With its bioactive component and fiber content, this product may be classified as functional food which may help improving consumer health.